Aesthetic dentistry and ethics: a systematic review of marketing practices and overtreatment in cosmetic dental procedures - Masoumeh Rostamzadeh; Farshad Rahimi (BMC Medical Ethics)
Abstract Background The increasing societal emphasis on physical appearance, particularly influenced by social media, has led to a significant rise in demand for aesthetic dentistry procedures. This study aims to explore the ethical dimensions of marketing practices and the phenomenon of overtreatment in cosmetic dental procedures, highlighting the implications for patient care and professional integrity. Methods A systematic literature review was conducted across four databases, yielding an initial 76 articles. After applying inclusion and exclusion criteria, 12 articles were selected for analysis. The review focused on ethical considerations, marketing practices, and overtreatment in aesthetic dentistry, employing narrative synthesis to extract relevant data. Results The findings indicate that social media is a primary driver of patient expectations, often prioritizing aesthetic outcomes over health considerations. This trend raises ethical concerns about informed consent and autonomy. The commodification of dental care, fueled by aggressive marketing strategies, has resulted in a notable increase in overtreatment, where unnecessary procedures are performed to satisfy commercial pressures and idealized beauty standards. The review highlights a lack of robust ethical guidelines governing marketing practices in aesthetic dentistry, exacerbating these issues. Conclusions The study underscores the urgent need for clear ethical frameworks to guide dental practitioners in balancing patient welfare with business interests. Recommendations include the implementation of ethics education in dental curricula, the development of comprehensive ethical guidelines, and fostering open communication between practitioners and patients. These measures are essential for enhancing informed decision-making and ensure that patient care remains the priority in aesthetic dentistry.